압력 센서용 탄소 나노 튜브 폴리머 복합체의 필러 함량과 종횡비에 따른 압저항 특성 - 유종찬; Jongchan Yoo; 김동영; Dong-young Kim; 이동관; Dong-kwan Lee; 남건우; Kunwoo Nam; 박성훈; Sung-hoon Park (대한금속·재료학회지, 61(10), 2023)
Polymer composites enriched with conductive fillers hold immense potential for flexible pressure sensors, because of the remarkable piezoresistive effect they possess. Research on polymer composite pressure sensors has been actively ongoing because of their flexibility and high electrical resistance performance. This paper presents a comprehensive comparison of the piezoresistive characteristics of conductive composites for pressure sensors, focusing on the influence of carbon nanotube (CNT) content and aspect ratio. Polymer composites with conductive fillers, specifically CNTs, have demonstrated significant potential for pressure sensing applications based on the piezoresistive effect. By systematically varying the CNT concentration and aspect ratio, we investigated the impact of these parameters on the piezoresistive behavior of the composites. A pressure in the range of 0-200 kPa was applied to the conductive composite, and resistance change due to pressing was measured. The best performing samples were evaluated in 150 cycle tests to verify repeatability and durability. Experimental analysis and characterization revealed the intricate relationship between CNT content, aspect ratio, and the resulting piezoresistive properties. Through this study, we aim to enhance understanding of how CNT concentration and aspect ratio influence the performance of CNT/PDMS composites as pressure sensors, thereby facilitating the development of optimized sensing materials for various pressure sensing applications. (Received 8 June, 2023; Accepted 5 July, 2023)